Shen-Bai-Jie-Du decoction suppresses the progression of colorectal adenoma to carcinoma through regulating gut microbiota and short-chain fatty acids - Min Huang; Ye Zhang; Mingxin Ni; Meng Shen; Yuquan Tao; Weixing Shen; Dongdong Sun; Liu Li; Changliang Xu; Jiani Tan; Yueyang Lai; Chengtao Yu; et al. (Chinese Medicine, 2024)
Abstract Background Shen-Bai-Jie-Du decoction (SBJDD), a traditional Chinese herb formula developed based on evidence-based medicine, is efficacy to reduce the recurrence and carcinogenesis of colorectal adenoma. However, the mechanism of SBJDD to treat colorectal adenoma remains unclear. The present study aims to investigate the efficacy and mechanism of SBJDD on colorectal adenoma carcinogenesis from the aspects of regulating gut microbiota and short-chain fatty acids (SCFAs). Methods Twenty-one patients diagnosed with colorectal adenoma were recruited in the study and required to take SBJDD for four consecutive weeks. Analysis of gut microbiota was conducted using 16S rRNA gene amplicon sequencing, while levels of SCFAs in fecal and serum samples were determined through HPLC–MS/MS. Additionally, twenty-four Apcmin/+ mice were randomly assigned to normal diet (ND), high-fat diet (HFD), and SBJDD groups. The pharmacological effects and mechanism of SBJDD on colorectal adenoma carcinogenesis were assessed using RT-qPCR, HE staining, IHC staining, Western blot, IF staining, and Flow cytometry assays. Results Our clinical study has shown that SBJDD can regulate the gut microbiota composition and enhance SCFAs production in patients with colorectal adenoma. SBJDD alleviated colorectal adenoma formation and carcinogenesis, as well as protected the integrity of the intestinal barrier in the Apcmin/+ mice model compared to the HFD group. Additionally, SBJDD was found to regulate gut microbiota capable of producing SCFAs. G protein-coupled receptors GPR43, GPR41, and GPR109a were effectively activated in the SBJDD group, while HDAC1 and HDAC3 were inhibited. Furthermore, decreased expression levels of interleukin 1 beta (IL-1β) and interleukin 6 (IL-6), along with elevated expression level of interleukin 10 (IL-10), were observed in the colorectal tissue of the SBJDD group. Finally, SBJDD exhibited the ability to reduce the proportion of M1-type macrophages while increasing the proportion of M2-type macrophages. Conclusions Our study objectively demonstrated the pharmacological effects of SBJDD in inhibiting the progression of colorectal adenoma and investigated its mechanisms in terms of regulating gut microbiota, increasing SCFAs, and reducing colorectal inflammation.